Peningkatan Kemampuan Kehumasan, CSR, dan Public Speaking bagi Siswa SMA di Kepulauan Seribu - GM Soekowati GM Soekowati; Muhamad Rosit; Euis Nurul Bahriyah; Kevin Ramadan; Diana AnggraenI (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This community service activity aims to improve the knowledge and understanding of students at SMAN 69 Kepulauan Seribu regarding the role of public relations, Corporate Social Responsibility (CSR), public speaking, and the relationship between companies and communities within the framework of sustainable development. This program is designed to address the need for PR literacy in island areas with limited access to information and to strengthen the capacity of the younger generation to understand the role of CSR in community development, humanitarianism, and sustainability. The methods used include education, training, discussions, and PR simulations based on case studies of companies operating in coastal areas. The results of the activity indicate an increase in students' understanding of PR concepts, corporate image, awareness of the importance of collaboration between companies and communities for social and environmental sustainability. This program has had a positive impact on students' critical awareness and strengthened the school's relationships with stakeholders.ABSTRAKKegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan pemahaman siswa SMAN 69 Kepulauan Seribu dan MAN 1 Kepulauan Seribu mengenai kehumasan (public relations), Corporate Social Responsibility (CSR), public speaking, dan hubungan antara perusahaan dan masyarakat dalam kerangka pembangunan berkelanjutan. Program ini dirancang untuk menjawab kebutuhan literasi PR di daerah kepulauan yang memiliki keterbatasan akses informasi dan menguatkan kapasitas generasi muda dalam memahami peran CSR dalam pengembangan masyarakat, kemanusiaan, dan sustainability. Metode yang digunakan adalah menyelenggarakan edukasi, pelatihan, diskusi, dan simulasi kehumasan berbasis studi kasus tentang perusahaan yang beroperasi di wilayah pesisir. Hasil kegiatan menunjukkan peningkatan pemahaman siswa mengenai konsep humas, citra perusahaan, serta kesadaran akan pentingnya kolaborasi antara perusahaan dan masyarakat dalam keberlanjutan sosial maupun lingkungan. Program ini memberikan dampak positif terhadap kesadaran kritis siswa dan memperkuat hubungan sekolah dengan pihak-pihak pemangku kepentingan.